Zn2+ Induced Phase Transformation of K2MnFe(CN)6 Boosts Highly Stable Zinc‐Ion Storage. Issue 31 (27th June 2021) - Deng, Wenjun; Li, Zhengang; Ye, Yaokun; Zhou, Zhuqing; Li, Yibo; Zhang, Man; Yuan, Xinran; Hu, Jun; Zhao, Wenguang; Huang, Zhongyuan; Li, Chang; Chen, Haibiao; et al.
Abstract: Prussian blue analogues (PBAs), featuring an open framework for accommodating large ions and tunable valence states, have garnered wide interest in the context of aqueous zinc‐ion batteries (ZIBs). However, PBAs in ZIBs currently still suffer from low capacity and poor cycling stability due to structural instability. Here a K2 MnFe(CN)6 cathode achieving a very stable capacity of 100 mAh g −1 is reported in a ZIB charged/discharged to 400 cycles. Interestingly, such a stable capacity is attributed to the fact that the K2 MnFe(CN)6 cathode is gradually transformed to rhombohedral K2 Zn3 [Fe(CN)6 ]2, a process that is induced by Zn 2+ insertion. The mechanism of the phase transformation is further investigated through ab initio calculations and detailed characterizations. The inserted Zn 2+ is found to induce an intense Jahn‐Teller effect of the trivalent manganese, resulting in a strong lattice distortion. Coupled with the disproportionation reaction of manganese, the MnN6 octahedra are replaced by ZnN4 tetrahedra and produce the new K2 Zn3 [Fe(CN)6 ]2 phase eventually. The robust structure of the resulting K2 Zn3 [Fe(CN)6 ]2 phase contains wider channels for accommodating divalent ions and thus enables highly stable and reversible storage of Zn 2+ ions. The findings of this work lead to a new understanding on the evolution of PBAs in ZIBs, and provide a promising cathode material. Abstract : Prussian blue analogue compounds always provide low specific capacity (typically less than 80 mAh g −1 ) for zinc‐ion batteries. In addition, the uncontrolled phase transition arising from inserted Zn 2+ gives rise to cyclic fading. Here it is found that a high‐capacity and stable K2 MnFe(CN)6 )‐Zn aqueous hybrid‐ion battery can be achieved through a complete phase transformation which arises from an intensified Jahn‐Teller effect.